Strategi pelayanan dan teknologi informasi pada bank syariah : analisis efektivitas layanan digital banking dalam meningkatkan loyalitas nasabah bank syariah - Ariwibowo, Yusuf Ageng (Maliki Interdisciplinary Journal, 2025)
The development of information and communication technology (ICT) has significantly transformed various sectors, including Islamic banking. Islamic banks in Indonesia are increasingly adopting digital transformation to respond to the growing demands of modern customers who value convenience, transparency, and efficiency. One of the most prominent innovations is the implementation of digital banking, which serves not only as a financial transaction platform but also as a means of building long-term relationships between banks and customers, grounded in Islamic values such as honesty (shidq), justice (‘adl), and trustworthiness (amanah). This study aims to analyze the effectiveness of service strategies based on information technology in enhancing customer loyalty in Indonesian Islamic banks. The main focus is to explore how digital banking implementation can strengthen customer trust, satisfaction, and loyalty through the synergy between technological innovation and Sharia principles. This research employs a descriptive qualitative approach through a comprehensive literature review of academic journals, annual reports from Islamic banks, and secondary data published by the Financial Services Authority (OJK). The analysis identifies several key dimensions of technology-based service strategies, including system reliability, ease of use, transaction security, and digital service quality.